Gastrointestinal Stromal Tumor Mimicking Ovarian Tumor - Özlem Seçilmiş Kerimoğlu; Füsun Baba; Aybike Tazegül; Hüsnü Alptekin; Hasan Acar; Çetin Çelik (Medical Network, 2012)
Malignant gastrointestinal stromal tumors are rare mesenchymal tumors originating from the gastrointestinal tract. Making a differential diagnosis with gynecologic masses may be difficult in the preoperative period. The patient was a 45- year-old woman who presented to our clinic with a palpable mass filling the pelvis. The CA 125 value was 42.7 U/ml. She underwent right hemicolectomy, total omentectomy, total abdominal hysterectomy, bilateral salpingo-oophorectomy and bilateral pelvic and para-aortic lymph node dissection since the frozen section assessment of the biopsy from the right colon was reported as a tumoral mass probably originating from the ovary. Tumoral tissue showed diffuse cytoplasmic membraneous staining immunohistochemically with CD117, showed strong focal strong cytoplasmic staining with SMA. It was stained negative with desmin, S-100 and CD34. Molecular analysis of KIT gene was performed, we didn't detect mutations of exon 9 or 11. Surgical exploration of pelvic masses with undetermined origins should be performed in multidiciplinary hospitals including gynecological oncology and surgical oncology teams. Histopathological examinations should be performed by experienced pathologists.